Sustainable behaviors and personality moderating the status goal and purchase intention relationship of luxury brands - Vera-Martínez, Jorge; Fuentes, Humberto; Kolbe, Diana (Journal of Business Economics and Management, 2024)
Luxury brands are related to two major mechanisms of social adaptation: value-expressive and social-adjustive. Researchers have established that these two functions are likely to influence customer purchase intention. Additionally, evidence suggests an interaction between sustainability beliefs and personality traits. Traditional, luxury brand purchasers are considered carefree of sustainability considerations. Therefore, a research gap exists regarding sustainable behaviors and personality issues in relation to luxury brands. Thus, building on a model of the effects of the value-expressive and social-adjustive functions of luxury brands on purchase intention, this study analyzes the effects of two types of moderating variables, namely, sustainable consumption (anthropocentrism, perceived self-efficacy, ecological behavior, conservatism, and egoism) and personality traits (conscientiousness, extraversion, openness, and neuroticism). Results of a structural equation modeling analysis with nested models, using a sample of 299 U.S. luxury car consumers, reveal that for the value-expressive and purchase intention relationship, only perceived self-efficacy shows a negative moderating effect. Meanwhile, for the relationship between social-adjustive and purchase intention, anthropocentrism, egoism, extraversion, and neuroticism demonstrate moderating effects. Thus, the variables here proposed primarily moderate the social-adjustive and purchase intention relationship. Therefore, luxury product firms pursuing a long-term sustainability agenda may benefit from strategies based on social-adjustive needs.